Examining Inclusive Democracy: The Political Rights Of People With Intellectual Disabilities In Indonesia (Asian Journal of Law and Humanity, 2026)
This study examines the fulfilment of political rights for people with intellectual disabilities in the 2024 Indonesian General Election, focusing on the urban-coastal context of Pekalongan City. Despite formal constitutional guarantees and the landmark Constitutional Court Ruling No. 135/PUU-XIII/2015—which removed voting barriers for citizens with mental and intellectual disabilities—substantive inclusion remains in a highly fragile state. Using empirical legal methods and a socio-legal approach, this study examines the gap between the normative democratic framework and the sociological reality at polling stations (TPS). Data were collected through in-depth interviews with the General Election Commission (KPU), disability organisations (PPDI), and families of voters with intellectual disabilities. By applying Amartya Sen’s Capabilities Approach and Social Citizenship Theory, this study reveals that voters with intellectual disabilities face systemic “substantive exclusion” characterised by a lack of cognitive accessibility in polling materials, as well as the persistence of patron-client voting patterns dominated by family guardians. This article argues that true democratic inclusivity must go beyond formal administrative procedures by incorporating easily readable visual standards and supported decision-making models. Finally, this research proposes a collaborative electoral governance model to transition the voting system for people with disabilities from mere symbolic inclusion to dignified, rights-based political participation